O Caso default no português do Brasil: revisitando o Caso dos inacusativos (Revista de Estudos da Linguagem, 2005)
The goal of this paper is to investigate the contexts in BrazilianPortuguese in which DPs are marked with nominative default Case,and to analyse the possibility of attributing default Case to the DPsin post-verbal position of sentences built with inaccusative verbs.The claim is that, if the verb shows agreement features, such DPswill check the nominative Case in the syntax; if the verb isuninflected for person and number, such DPs will receive a defaultCase marking in the morphological component.